High SERS performance of functionalized carbon dots in the detection of dye contaminants - Yanqiu Yang; Lingru Kong; Yong Ding; Lixin Xia; Shuo Cao; Peng Song (Journal of Advanced Research)
Introduction: The long-term overuse of malachite green (MG) has potential carcinogenic, teratogenic, and mutagenic effects. The functional nanocomposite is novel and challenging to construct and implement through surface enhanced Raman scattering (SERS) strategy to reveal the contributions in application. Objectives: The novel Ag-CDs (carbon dots)-PBA (phenyl boric acid) nanocomposite was constructed by a facile route to detect toxic MG molecule with high SERS sensitivity and good uniformity. Methods: The enhanced substrate used for the detection of MG has been successfully constructed using PBA modulated Ag-CDs on a structured surface with rich binding sites. Results: The fabricated Ag-CDs-PBA substrate can be used to analyze various probe molecules exhibiting high sensitivity, good signal reproducibility, and excellent stability. The mechanism between components has been proved by calculations originating from the plasmonic Ag and active electronic transmission among the bridging CDs and PBA via the close spatial π-π effect. In addition, the accelerated separation of electron-hole pairs was triggered to further improve the SERS activity of the hybrid via a bidirectional charge transfer (CT) process. Significantly, the Ag-CDs-PBA system shows distinctive selectivity, in which PBA can hinder the interference of other species without specific hydroxyl groups. Conclusion: Based on this deeper insight on plasmon-mediated mechanism, the SERS substrate was successfully practiced for quantitative determination in real water and fish samples. The strategy developed promises to be a new sensor technology and has great potential for environmental and food safety applications.